Model of The Determinants of School Participation Rates in Banyuwangi Regency: An Application of System Dynamic Analysis - Suhartono Winoto; Mohammad Said; Erlita Cahyasari; Nurjati Widodo; Rendra Eko Wismanu (Yayasan Keluarga Guru Mandiri, 2022)
Education is one of the priority basic services for human resource development. There are two indicators to measure the success in education, known as the accessibility of education and the quality of education. Efforts to determine the level of success of the Government in opening access to education services can be identified from several indicators. These indicators are a benchmark for the success of the Government in opening access to education for the entire community, especially those related to the School Participation Rate. This study aims to determine the existing conditions and analyze the forecasting of determinant factors that affect the achievement of school participation rates in Banyuwangi Regency. This study used a qualitative method with a dynamic system approach. The results showed that the school participation rate in Banyuwangi Regency was influenced by several determinant factors that were interrelated with each other. Based on the existing conditions, there was a need to improve all of the determinant factors. However, an increase in poverty factor as an impact of COVID-19 has encouraged government to provide an alternative policies to avoid the decrease in school participation rates. The results of the forecasting simulation for the next 20 years showed that the behaviour of time from the school participation rate will be in line with the increase in determinant factors in education system, while the results of forecasting education quality showed that within next 20 years, there will be a significant increase in the first two years of the simulation, then there will be an increase in slopes in the opposite direction from the school participation rate and accompanied by an increase in other elements that run in the education system in Banyuwangi Regency.